2017
DOI: 10.1073/pnas.1615105114
|View full text |Cite
|
Sign up to set email alerts
|

Cdon deficiency causes cardiac remodeling through hyperactivation of WNT/β-catenin signaling

Abstract: On pathological stress, Wnt signaling is reactivated and induces genes associated with cardiac remodeling and fibrosis. We have previously shown that a cell surface receptor Cdon (cell-adhesion associated, oncogene regulated) suppresses Wnt signaling to promote neuronal differentiation however its role in heart is unknown. Here, we demonstrate a critical role of Cdon in cardiac function and remodeling. Cdon is expressed and predominantly localized at intercalated disk in both mouse and human hearts. Cdon-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 68 publications
0
49
0
Order By: Relevance
“…The expression of CX43 in CCs around matured oocytes was significantly higher than that of immature oocytes (Li et al, ). Furthermore, expression level of Cx43 regulated by Wnt/β‐catenin signalling pathway (Heyden et al, ; Jeong et al, ; Le et al, ; Wang, Song, Liu, & Zhao, ) was one of marked for oocytes maturation, and its function required the phosphorylation modified of CK1 (Cooper & Lampe, ).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of CX43 in CCs around matured oocytes was significantly higher than that of immature oocytes (Li et al, ). Furthermore, expression level of Cx43 regulated by Wnt/β‐catenin signalling pathway (Heyden et al, ; Jeong et al, ; Le et al, ; Wang, Song, Liu, & Zhao, ) was one of marked for oocytes maturation, and its function required the phosphorylation modified of CK1 (Cooper & Lampe, ).…”
Section: Introductionmentioning
confidence: 99%
“…Both canonical and non-canonical Wnt signalling have been implicated in the multistep process of cardiogenesis (Gessert & Kühl, 2010;Jeong et al, 2017;Mazzotta et al, 2016), however, understanding of the outcome of activating and inhibiting the Wnt pathways at specific times during the development of the heart is still not fully understood. Our data seems to favour the hypothesis that in the heart, PDZRN3 is acting in the PCP pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt activity is normally low in the adult organism, and it is generally believed that it is reactivated under pathological conditions. It was reported that Wnt signaling is activated shortly after myocardial infarction and is significantly associated with cardiac remodeling and fibrosis [36][37][38]. Duan et al found that the canonical Wnt/β-catenin pathway was activated after acute ischemic myocardial injury in mice.…”
Section: Role Of Sfrp2 In Cardiac Fibrosismentioning
confidence: 99%